Cobalt sulfide/N, S codoped porous carbon core–shell nanocomposites as superior bifunctional electrocatalysts for oxygen reduction and evolution reactions. Issue 48 (24th November 2015) - Chen, Binling; Li, Rong; Ma, Guiping; Gou, Xinglong; Zhu, Yanqiu; Xia, Yongde
Abstract : Core–shell cobalt sulphide/N, S-codoped porous carbon nanocomposites exhibit excellent electrocatalytic activities in both ORR and OER with superior durability. Abstract : Exploring highly-efficient and low-cost bifunctional electrocatalysts for both oxygen reduction reaction (ORR) and oxygen evolution reactions (OER) in the renewable energy area has gained momentum but still remains a significant challenge. Here we present a simple but efficient method that utilizes ZIF-67 as the precursor and template for the one-step generation of homogeneous dispersed cobalt sulfide/N, S-codoped porous carbon nanocomposites as high-performance electrocatalysts. Due to the favourable molecular-like structural features and uniform dispersed active sites in the precursor, the resulting nanocomposites, possessing a unique core–shell structure, high porosity, homogeneous dispersion of active components together with N and S-doping effects, not only show excellent electrocatalytic activity towards ORR with the high onset potential (around −0.04 V vs. −0.02 V for the benchmark Pt/C catalyst) and four-electron pathway and OER with a small overpotential of 0.47 V for 10 mA cm −2 current density, but also exhibit superior stability (92%) to the commercial Pt/C catalyst (74%) in ORR and promising OER stability (80%) with good methanol tolerance. Our findings suggest that the transition metal sulfide–porous carbon nanocomposites derived from the one-step simultaneous sulfurization and carbonization of zeolitic imidazolate frameworks are excellent alternative bifunctional electrocatalysts towards ORR and OER in the next generation of energy storage and conversion technologies.